Analisis Faktor-Faktor yang Mempengaruhi Volume Impor Tekstil dan Produk Tekstil di Indonesia Periode 1989-2018 - Luhur Jalu Tawaqal; Arif Pujiyono (Universitas Diponegoro, 2021)
This research aims to analyze factors that influencing the textile and clothing import volume in Indonesia. The implementation of the 4.0 industrial revolution globally will certainly affect the textile industry and textile products in Indonesia. This research is using an error correction model (ECM) because ECM is the most frequently used approach to analyze time-series data. Also, using structure, conduct, performance paradigm to identify the characteristics of the textile and clothing industry. The data used is secondary data and has taken from credible institutions like Badan Pusat Statistik (BPS), Bank Indonesia (BI), and World Bank within 1989-2018 period. The CR4 value is 9,93 percent indicate that the structure of the textile and clothing industry is an oligopoly. PCM and XEF value shows that the textile and clothing industry in Indonesia has been managed quite well. The variable for the error correction model is import volume for dependent variable and price for imported textiles, price for domestic textiles, GDP, exchange rate, and population. Results shows that in the short term price of imported textile, GDP and exchange rate has a significant effect while the price for domestic textile and population has no significant effect. In the long term, GDP and population have a significant effect while the price of imported textiles, price for domestic textiles, and the exchange rate has no significant effect.